Direct and Selective C‐H Carbamoylation of (Hetero)aromatics with TMSOTf‐Activated Carbamoyl Chloride. Issue 1 (20th November 2018) - Uehara, Ayaka; Olivero, Sandra; Michelet, Bastien; Martin‐Mingot, Agnès; Thibaudeau, Sébastien; Duñach, Elisabet
Abstract : Exploiting trimethylsilyltrifluoromethanesulfonate as Lewis acid, (hetero)aromatics underwent regioselective and direct carbamoylation. The method is based on the in situ generation of a highly electrophilic carbamoyl triflate active species. Abstract : TMSOTf acts as Lewis acid to activate carbamoyl chlorides and generates highly electrophilic carbamoyl triflates in situ; these are active species for late‐stage aromatic carbamoylation.